Low-temperature elastic properties of Zr₅₅Al₁₀Ni₅Cu₃₀ bulk metallic glass doped with yttrium - Bakai, S.A.; Bulatov, A.S.; Dolzhenko, V.F.; Klochko, V.S.; Korniyets, A.V.; Spitsyna, V.I. (Functional Materials, 2015)
The temperature dependence of elastic constants cij(T) of zirconium Zr₅₅Al₁₀Ni₅Cu₃₀-based, 1 % yttrium-doped bulk metallic glass (BMG) within the temperature range of 78 to 300 K was examined using the method of resonance spectroscopy. The measurements helped determine low-temperature behavior of elastic Young's modulus (E), shear modulus (G) and bulk modulus. BMG doping with yttrium allowed to obtain high value of the Poisson's ratio (σ) and the B/G ratio and note weak dependence of B(T) stemming from the appearance of an efficient dense pack of atomic clusters with icosahedral ordering symmetry within their internal structure. It was discovered that under 300 K, 1 % of yttrium reduces E by 5.4 % in comparison with the size of original BMG matrix. Analysis of the Debye temperature (θD) pattern points out the predominant contribution of phonon anharmonicity to BMG's elastic properties. It was assumed that high value of the Gruneisen parameter (γ) is due to manifestation of particularities of oscillatory properties.